Effectiveness of orthodontic temporary anchorage devices in canine retraction and anchorage preservation during the two-step technique: a systematic review and meta-analysis - Tian, Haonan (BMC Oral Health, 2020)
BACKGROUND: Temporary anchorage devices have been used for decades in orthodontic practice for many applications. The aim of this systematic review was to assess the effectiveness of orthodontic temporary anchorage devices in canine retraction during the two-step technique. METHODS: A search was systematically performed for articles published prior to June 30, 2019 in five electronic databases (PubMed, Embase, Cochrane Central Register of Controlled Trials, Web of Science, Scopus). The risk of bias was assessed using the Cochrane risk of bias tool for randomized controlled trials (RCTs) and the risk of bias in nonrandomized studies of interventions (ROBINS-I) tool for controlled clinical trials (CCTs). The Grading of Recommendation, Assessment, Development and Evaluation (GRADE) approach was used for the quality assessment. Data concerning the mean difference in mesial molar movement and extent of canine retraction were extracted for statistical analysis. The mean differences and 95% confidence intervals were analyzed for continuous data. A meta-analysis with a random-effects model for comparable outcomes was carried out. RESULTS: Three RCTs and five CCTs were finally included. Meta-analysis showed a significant increase not only in anchorage preservation in the implant anchorage group in both the maxilla (1.56 mm, 95% CI: 1.14 to 1.98, P < 0.00001) and the mandible (1.62 mm, 95% CI: 1.24 to 2.01, P < 0.00001) but also in canine retraction in the implant anchorage group in both the maxilla (0.43 mm, 95% CI: 0.16 to 0.69, P = 0.001) and the mandible (0.26 mm, 95% CI: 0.02 to 0.49, P = 0.03). CONCLUSIONS: There is very low-quality evidence showing that implant anchorage is more efficient than conventional anchorage during canine retraction. Additional high-quality studies are needed.